Review: Current applications and challenges for liquid chromatography coupled to isotope ratio mass spectrometry (LC/IRMS). - Godin, J; McCullagh, J (2011)
High-precision isotope analysis is recognized as an essential research tool in many fields of study. Until recently, continuous flow isotope ratio mass spectrometry (CF-IRMS) was available via an elemental analyzer or a gas chromatography inlet system for compound-specific analysis of light stable isotopes. In 2004, however, an interface that coupled liquid chromatography with IRMS (LC/IRMS) became commercially available for the first time. This brought the capability for new areas of application, in particular enabling compound-specific δ(13)C analysis of non-volatile, aqueous soluble, compounds from complex mixtures. The interface design brought with it several analytical constraints, however, in particular a lack of compatibility with certain types of chromatography as well as limited flow rates and mobile phase compositions. Routine LC/IRMS methods have, however, been established for measuring the δ(13)C isotopic ratios of underivatized individual compounds for application in archeology, nutrition and physiology, geochemistry, hydrology, soil science and food authenticity. Seven years after its introduction, we review the technical advances and constraints, methodological developments and new applications of liquid chromatography coupled to isotope ratio mass spectrometry.